The MAMs Structure and Its Role in Cell Death - Nan Wang; Chong Wang; Hongyang Zhao; Yichun He; Beiwu Lan; Liankun Sun; Yufei Gao (Cells, 2021)
The maintenance of cellular homeostasis involves the participation of multiple organelles. These organelles are associated in space and time, and either cooperate or antagonize each other with regards to cell function. Crosstalk between organelles has become a significant topic in research over recent decades. We believe that signal transduction between organelles, especially the endoplasmic reticulum (ER) and mitochondria, is a factor that can influence the cell fate. As the cellular center for protein folding and modification, the endoplasmic reticulum can influence a range of physiological processes by regulating the quantity and quality of proteins. Mitochondria, as the cellular “energy factory,” are also involved in cell death processes. Some researchers regard the ER as the sensor of cellular stress and the mitochondria as an important actuator of the stress response. The scientific community now believe that bidirectional communication between the ER and the mitochondria can influence cell death. Recent studies revealed that the death signals can shuttle between the two organelles. Mitochondria-associated membranes (MAMs) play a vital role in the complex crosstalk between the ER and mitochondria. MAMs are known to play an important role in lipid synthesis, the regulation of Ca2+ homeostasis, the coordination of ER-mitochondrial function, and the transduction of death signals between the ER and the mitochondria. Clarifying the structure and function of MAMs will provide new concepts for studying the pathological mechanisms associated with neurodegenerative diseases, aging, and cancers. Here, we review the recent studies of the structure and function of MAMs and its roles involved in cell death, especially in apoptosis.